Sex Differences on Social and Anxiety-Related Responses in Low-Density Lipoprotein Receptor Knockout Mice - Cibele Martins Pinho; Gislaine Olescowicz; Laura Menegatti Bevilacqua; Gabriel Estevam Santos de Amorim; Nicolle Platt; Marcos Antonio da Silva Räder; Francisco da Silveira Neto; Manuella Pinto Kaster; Rui Daniel Prediger (Molecular Neurobiology, 2026)
Familial hypercholesterolemia, caused by mutations in the low-density lipoprotein receptor (LDLr), is associated with cognitive and affective disturbances. However, sex differences in the impact of LDLr deficiency on anxiety and social behaviors remain poorly characterized. Male and female LDLr⁻/⁻ and wild-type (WT) C57BL/6 mice (4–5 months old) underwent a battery of behavioral tests assessing locomotion, anxiety-like behavior (open field, elevated plus maze, marble-burying test), and sociability (social interaction and three-chamber test). Serum cholesterol levels and catechol-O-methyltransferase (COMT) levels in the prefrontal cortex (PFC) and amygdala (AMY) were subsequently analyzed by Western blotting. Both male and female LDLr⁻/⁻ mice displayed marked hypercholesterolemia relative to WT controls. Female LDLr⁻/⁻ mice exhibited hyperlocomotion and reduced anxiety-like behavior in multiple tasks. Both sexes demonstrated increased sociability, although with test- and sex-dependent variations. Neurochemical analysis revealed a selective reduction of COMT in the PFC of LDLr⁻/⁻ females, suggesting sex-specific dopaminergic modulation underlying the behavioral phenotypes. LDLr deficiency induced sex-dependent changes in locomotor, anxiety-related, and social behaviors, accompanied by altered COMT expression in corticolimbic regions. These findings reveal an association between LDL receptors, dopaminergic regulation, and socio-emotional behaviors, emphasizing the relevance of social characterization in the neurobehavioral assessment of dyslipidemia. Graphical Abstract

A critical analysis on the concentrations of phenolic compounds tested using in vitro and in vivo Parkinson’s disease models - José Messias Perdigão; Bruno José Brito Teixeira; Vinicius Carvalho-da-Silva; Rui Daniel Prediger; Rafael Rodrigues Lima; Herve Rogez (Critical Reviews in Food Science and Nutrition, 2024)

Increased ATP Release and Higher Impact of Adenosine A2A Receptors on Corticostriatal Plasticity in a Rat Model of Presymptomatic Parkinson’s Disease - Francisco Q. Gonçalves; Filipe C. Matheus; Henrique B. Silva; Joana I. Real; Daniel Rial; Ricardo J. Rodrigues; Jean-Pierre Oses; António C. Silva; Nélio Gonçalves; Rui D. Prediger; Ângelo R. Tomé; Rodrigo A. Cunha (Molecular Neurobiology, 2023)
Extracellular ATP can be a danger signal, but its role in striatal circuits afflicted in Parkinson’s disease (PD) is unclear and was now investigated. ATP was particularly released at high stimulation intensities from purified striatal nerve terminals of mice, which were endowed with different ATP-P2 receptors (P2R), although P2R antagonists did not alter corticostriatal transmission or plasticity. Instead, ATP was extracellularly catabolized into adenosine through CD73 to activate adenosine A 2A receptors (A 2A R) modulating corticostriatal long-term potentiation (LTP) in mice. In the presymptomatic phase of a 6-hydroxydopamine rat model of PD, ATP release from striatal nerve terminals was increased and was responsible for a greater impact of CD73 and A 2A R on corticostriatal LTP. These observations identify increased ATP release and ATP-derived formation of extracellular adenosine bolstering A 2A R activation as a key pathway responsible for abnormal synaptic plasticity in circuits involved in the onset of PD motor symptoms. The translation of these findings to humans prompts extending the use of A 2A R antagonists from only co-adjuvants of motor control in Parkinsonian patients to neuroprotective drugs delaying the onset of motor symptoms.

Neonatal Isoflurane Exposure in Rats Impairs Short-Term Memory, Cell Viability, and Glutamate Uptake in Slices of the Frontal Cerebral Cortex, But Not the Hippocampus, in Adulthood - Laíse Figueiredo de Oliveira; Gabriela Godoy Poluceno; Tuane Bazanella Sampaio; Leandra Celso Constantino; Ana Paula Costa; Wagner Carbolin Martins; Tharine Dal-Cim; Karen Andrinéia de Oliveira; Fabiana Kalyne Ludka; Rui Daniel Prediger; Frederico C. Pereira; Carla Inês Tasca (Neurotoxicity Research, 2022)

Caffeine Consumption plus Physical Exercise Improves Behavioral Impairments and Stimulates Neuroplasticity in Spontaneously Hypertensive Rats (SHR): an Animal Model of Attention Deficit Hyperactivity Disorder - Angela Patricia França; Marissa Giovanna Schamne; Bruna Soares de Souza; Débora da Luz Scheffer; Angelica Karina Bernardelli; Thiago Corrêa; Geison de Souza Izídio; Alexandra Latini; José Eduardo da Silva-Santos; Paula M. Canas; Rodrigo A. Cunha; Rui Daniel Prediger (Molecular Neurobiology, 2020)

Chronic Metabolic Derangement-Induced Cognitive Deficits and Neurotoxicity Are Associated with REST Inactivation - Aline Pertile Remor; Rodrigo Augusto da Silva; Filipe José de Matos; Viviane Glaser; Roberta de Paula Martins; Karina Ghisoni; Débora da Luz Scheffer; Denise Carleto Andia; Daniele Portinho; Ana Paula de Souza; Paulo Alexandre de Oliveira; Rui Daniel Prediger; et al. (Molecular Neurobiology, 2019)

The Gender-Biased Effects of Intranasal MPTP Administration on Anhedonic- and Depressive-Like Behaviors in C57BL/6 Mice: the Role of Neurotrophic Factors - Marissa Giovanna Schamne; Josiel Mileno Mack; Morgana Moretti; Filipe Carvalho Matheus; Roger Walz; Laurence Lanfumey; Rui Daniel Prediger (Neurotoxicity Research, 2018)

Long-Term Neurobehavioral Consequences of a Single Ketamine Neonatal Exposure in Rats: Effects on Cellular Viability and Glutamate Transport in Frontal Cortex and Hippocampus - Tuane Bazanella Sampaio; Laíse Figueiredo de Oliveira; Leandra Celso Constantino; Ana Paula Costa; Gabriela Godoy Poluceno; Wagner Carbolin Martins; Tharine Dal-Cim; Karen Andrinéia de Oliveira; Fabiana Kalyne Ludka; Rui Daniel Prediger; Carla Inês Tasca; Frederico C. Pereira (Neurotoxicity Research, 2018)

Succinobucol, a Non-Statin Hypocholesterolemic Drug, Prevents Premotor Symptoms and Nigrostriatal Neurodegeneration in an Experimental Model of Parkinson’s Disease - Danúbia Bonfanti Santos; Dirleise Colle; Eduardo Luiz Gasnhar Moreira; Mariana Appel Hort; Marcelo Godoi; Gael Le Douaron; Antonio Luiz Braga; Jamil Assreuy; Patrick Pierre Michel; Rui Daniel Prediger; Rita Raisman-Vozari; Marcelo Farina (Molecular Neurobiology, 2017)

Temporal Dissociation of Striatum and Prefrontal Cortex Uncouples Anhedonia and Defense Behaviors Relevant to Depression in 6-OHDA-Lesioned Rats - Filipe C. Matheus; Daniel Rial; Joana I. Real; Cristina Lemos; Reinaldo N. Takahashi; Leandro J. Bertoglio; Rodrigo A. Cunha; Rui D. Prediger (Molecular Neurobiology, 2016)

Exercise Improves Cognitive Impairment and Dopamine Metabolism in MPTP-Treated Mice - Aderbal S. Aguiar; Samantha C. Lopes; Fabrine S. M. Tristão; Daniel Rial; Gisele de Oliveira; Cláudio da Cunha; Rita Raisman-Vozari; Rui D. Prediger (Neurotoxicity Research, 2016)

Effects of Agmatine on Depressive-Like Behavior Induced by Intracerebroventricular Administration of 1-Methyl-4-phenylpyridinium (MPP+) - Morgana Moretti; Vivian Binder Neis; Filipe Carvalho Matheus; Mauricio Peña Cunha; Priscila Batista Rosa; Camille Mertins Ribeiro; Ana Lúcia S. Rodrigues; Rui Daniel Prediger (Neurotoxicity Research, 2015)

Atorvastatin Prevents Cognitive Deficits Induced by Intracerebroventricular Amyloid-β1–40 Administration in Mice: Involvement of Glutamatergic and Antioxidant Systems - Wagner C. Martins; Vanessa Valgas dos Santos; Alessandra Antunes dos Santos; Samuel Vandresen-Filho; Tharine A. Dal-Cim; Karen A. de Oliveira; Claudia B. N. Mendes-de-Aguiar; Marcelo Farina; Rui Daniel Prediger; Giordano Gubert Viola; Carla I. Tasca (Neurotoxicity Research, 2015)

Interaction of Curcumin with Manganese May Compromise Metal and Neurotransmitter Homeostasis in the Hippocampus of Young Mice - Ariana Ern Schmitz; Paulo Alexandre de Oliveira; Luiz F. de Souza; Danilo Grünig Humberto da Silva; Samara Danielski; Danúbia Bonfanti Santos; Eduardo Alves de Almeida; Rui Daniel Prediger; Andrew Fisher; Marcelo Farina; Alcir Luiz Dafre (Biological Trace Element Research, 2014)